2009
DOI: 10.1111/j.1460-9568.2008.06573.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C and μ‐opioid receptor (MOPr) desensitization in tolerance to morphine in rat locus coeruleus neurons

Abstract: In morphine tolerance a key question that remains to be answered is whether l-opioid receptor (MOPr) desensitization contributes to morphine tolerance, and if so by what cellular mechanisms. Here we demonstrate that MOPr desensitization can be observed in single rat brainstem locus coeruleus (LC) neurons following either prolonged (> 4 h) exposure to morphine in vitro or following treatment of animals with morphine in vivo for 3 days. Analysis of receptor function by an operational model indicated that with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 49 publications
7
117
1
Order By: Relevance
“…A recent study by Bailey et al showed that μ-opioid receptor desensitization was observed in single rat brainstem locus coeruleus neurons following exposure to morphine in vitro and in vivo (16). Interestingly, their study found that μ-opioid receptor desensitization has a significant PKC-dependent component and that this desensitization underlies the maintenance of morphine tolerance (16).…”
Section: Effects Of the Pkc Inhibitor On The Development Of Morphine mentioning
confidence: 99%
“…A recent study by Bailey et al showed that μ-opioid receptor desensitization was observed in single rat brainstem locus coeruleus neurons following exposure to morphine in vitro and in vivo (16). Interestingly, their study found that μ-opioid receptor desensitization has a significant PKC-dependent component and that this desensitization underlies the maintenance of morphine tolerance (16).…”
Section: Effects Of the Pkc Inhibitor On The Development Of Morphine mentioning
confidence: 99%
“…Agonist concentrationresponse data from LC neurons were fitted to sigmoidal curves with variable slopes, with the bottom of the curve in each case being constrained to 0, for determination of agonist EC 50 and E max values and for graphical representation of the data. Parameters from this fitting were then used as initial values for fitting of the concentration-response data to the operational model of pharmacological agonism (Black and Leff, 1983;Bailey et al, 2009;McPherson et al, 2010)…”
Section: Drugs Morphine Hydrochloride Was Obtained From Mcfarlanmentioning
confidence: 99%
“…However, morphine induces receptor phosphorylation inefficiently and activates protein kinase C (PKC) via the G protein-dependent pathway (Bohn et al, 2002;Zheng et al, 2008a,b). The participation of activated PKC in receptor signal desensitization and tolerance development has been extensively reported (Bohn et al, 2002;Smith et al, 2002;Zheng et al, 2008b;Bailey et al, 2009;Chu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%